Design of a prospective, multicenter, global, cohort study of electromagnetic navigation bronchoscopy. Issue 1 (December 2016) - Folch, Erik; Bowling, Mark; Gildea, Thomas R.; Hood, Kristin; Murgu, Septimiu; Toloza, Eric; Wahidi, Momen; Williams, Terence; Khandhar, Sandeep
Abstract Background Electromagnetic navigation bronchoscopy (ENB) procedures allow physicians to access peripheral lung lesions beyond the reach of conventional bronchoscopy. However, published research is primarily limited to small, single-center studies using previous-generation ENB software. The impact of user experience, patient factors, and lesion/procedural characteristics remains largely unexplored in a large, multicenter study. Methods/Design NAVIGATE (Clin ica l Ev aluation of superDi mension™ Naviga tion System for Elect romagne tic Navigation Bronchoscopy) is a prospective, multicenter, global, cohort study. The study aims to enroll up to 2, 500 consecutive subjects presenting for evaluation of lung lesions utilizing the ENB procedure at up to 75 clinical sites in the United States, Europe, and Asia. Subjects will be assessed at baseline, at the time of procedure, and at 1, 12, and 24 months post-procedure. The pre-test probability of malignancy will be determined for peripheral lung nodules. Endpoints include procedure-related adverse events, including pneumothorax, bronchopulmonary hemorrhage, and respiratory failure, as well as quality of life, and subject satisfaction. Diagnostic yield and accuracy, repeat biopsy rate, tissue adequacy for genetic testing, and stage at diagnosis will be reported for biopsy procedures. Complementary technologies, such as fluoroscopy and endobronchial ultrasound, will be explored. Success rates of fiducial marker placement, dye marking, and lymph node biopsies will be captured when applicable. Subgroup analyses based on geography, demographics, investigator experience, and lesion and procedure characteristics are planned. Discussion Study enrollment began in April 2015. As of February 19, 2016, 500 subjects had been enrolled at 23 clinical sites with enrollment ongoing. NAVIGATE will be the largest prospective, multicenter clinical study on ENB procedures to date and will provide real-world experience data on the utility of the ENB procedure in a broad range of clinical scenarios. Trial registration ClinicalTrials.govNCT02410837 . Registered 31 March 2015.